Voices from the margins : an annotated bibliography of fiction on disabilities and differences for young people - Ward, Marilyn (Greenwood Press, 2002)
Young people who feel marginalized due to physical differences or disabilities may benefit from discovering fictional characters who face similar difficulties. This unique bibliography surveys the field of children's and young adult literature published since 1990, identifying 200 quality books that deal with a wide range of contemporary health and self-image topics.